Komunikacja interkulturowa na zajęciach z języka niemieckiego jako kolejnego po języku angielskim - Zuzok, Nadja (My University, 2014)
Podstawę pracy stanowiła chęć zbadania, czy w szkołach podstawowych w Polsce realizowane są sposoby nauczania języków obcych pozwalające na rozwijanie kompetencji interkulturowych uczniów, a jednocześnie wykorzystujące aspekty integracyjnej nauki języków obcych (w kolejności: język angielski jako pierwszy, język niemiecki jako drugi język obcy).

The author’s thesis is about aspects of acquiring intercultural competence at an elementary level during the process of learning German as a second foreign language after English. It shows the present situation and teaching infrastructure of German as a second foreign language at Polish elementary schools and points out the influence it can have on teaching and learning processes in the foreign language classroom in general. The presented data are based on the author’s numerous classroom observations and interviews conducted with Polish teachers of German.

Die vorliegende Doktorarbeit führt die Disziplinen Frühes Fremdsprachenlernen, Interkulturelle Kommunikation und Tertiärsprachendidaktik, speziell Deutsch nach Englisch, zusammen. Aufgrund der Untersuchungen, die an Grundschulen im Raum Poznań in den Klassen 4-6 durchgeführt wurden, sollte der Einfluss von Englisch auf Deutsch auf dem Gebiet des Interkulturellen gezeigt werden, wenn Deutsch als zweite Fremdsprache, speziell auch im frühen Fremdsprachenunterricht gelernt wird.
Intercultural Communication in Tertiary Language Teaching: German after English
Interkulturelle Kommunikation im Fremdsprachenunterricht Deutsch nach Englisch
Wydział Neofilologii: Instytut Lingwistyki Stosowanej
Keywords: Intercultural Communications; Interkulturelle Kommunikation; Tertiary language teaching; Interkulturelles Lernen; German after English; Deutsch nach Englisch; German as a foreign language; Tertiärsprachendidaktik; Früher Fremdsprachenunterricht